2004
DOI: 10.1530/eje.0.1500533
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of baseline body mass index under gonadotropin-suppressive therapy in girls with idiopathic precocious puberty

Abstract: Objective: To investigate longitudinally body mass index (BMI) evolution and obesity prevalence in a large and very homogeneous study population consisting only of girls with non-organic central precocious puberty (CPP) who were treated with gonadotropin-releasing hormone agonists (GnRHa) for at least two years. Patients and design: The 101 girls with idiopathic CPP who were selected for this study fulfilled the following inclusion criteria: (a) suppression of gonadotropin and gonadal sex steroid secretion dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 30 publications
9
66
1
3
Order By: Relevance
“…Chiumello et al suggested that girls with CPP undergo a shortened period of prepubertal lean mass development and so possess an insufficient lean body mass, leading to obesity. (Chiumello et al, 2000) Recently, Arrigo et al hypothesized that the pre-treatment increase in BMI is caused pubertal hormonal changes and secondary changes in body fat rather than CPP itself, as in their series they found that the suppression of pituitary-gonadal axis function was accompanied by a significant decrease in excess weight (Arrigo et al, 2004). However, our results showed that the suppression of the pituitary-gonadal axis did not bring about a significant change in excess weight, as described below.…”
Section: Discussionmentioning
confidence: 37%
See 2 more Smart Citations
“…Chiumello et al suggested that girls with CPP undergo a shortened period of prepubertal lean mass development and so possess an insufficient lean body mass, leading to obesity. (Chiumello et al, 2000) Recently, Arrigo et al hypothesized that the pre-treatment increase in BMI is caused pubertal hormonal changes and secondary changes in body fat rather than CPP itself, as in their series they found that the suppression of pituitary-gonadal axis function was accompanied by a significant decrease in excess weight (Arrigo et al, 2004). However, our results showed that the suppression of the pituitary-gonadal axis did not bring about a significant change in excess weight, as described below.…”
Section: Discussionmentioning
confidence: 37%
“…On the other hand, Arrigo et al reported 101 girls with CPP who received decapeptyl depot for over 2 years. (Arrigo et al, 2004) As described above, a quarter of the girls were classified as obese at the start of therapy, and only 4% of them were still obese at the end of therapy. BMI SDS did not increase in any of the patients during the therapy period.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Much less attention has been paid to changes in body composition. Some studies report an increase in fat mass or BMI during GnRH analogue treatment, with a return to values comparable to those at baseline after discontinuation (Pasquino et al, 2008;van der Sluis et al, 2002), whereas others report no changes (Palmert et al, 1999) or even a decreased BMI during GnRH analogue treatment (Arrigo et al, 2004). Lean body mass SDS decreases during GnRH analogue treatment (van der Sluis et al, 2002).…”
Section: Effects Of Gnrh Analogue Treatment On the Metabolic Profilementioning
confidence: 99%
“…Studies have focused on body composition, and were performed in children with CPP only. Some studies reported an increase in fat mass or body mass index (BMI) SDS during GnRHa treatment with a return to baseline values after discontinuation (1,2), whereas others reported no changes (3) or even a decreased BMI SDS during GnRHa treatment (4).…”
Section: Introductionmentioning
confidence: 99%